The Violence of Merging: Unica Zürn's Writing (on) the Body - Caroline Rupprecht (Studies in 20th & 21st Century Literature, 2003)
This article is about the work of German Surrealist Unica Zürn (1916-1970), known for her autobiographical text about madness, Der Mann im Jasmin: Eindrücke einer Geisteskrankheit (1977). The problem with Zürn's text, as this article demonstrates, is that it becomes nearly impossible to be distinguished from the author's life. Unlike conventional autobiographies, this text raises doubt oyer the sanity of the author who was not only diagnosed with schizophrenia but also made madness the subject of her writing. Zürn's companion, the artist Hans Bellmer, accused her of indulging in madness for the sake of being able to write about it; she herself wrote that it was the act of writing that drove her insane. Looking closely at the text, which plays with the differentiation between author, narrator, and character, and with the reader's expectations about the difference between reality and representation, it is not a symptom of mental illness but rather a carefully constructed work of art. Designed to convey the impression that its author is mentally ill, it explores the connection between madness and artistic production to raise questions of interpretation: How true to life is the work of art? How does art mediate or even create our understanding of life?— As this article concludes, Zürn contradicts the postmodern assumption that everything is a text by making extra-textual reality part of her writing, yet she also suggests that texts may become disturbingly real.